A suspended dive-net technique for catching territorial divers. Issue 1 (1st June 2016) - Uher-Koch, Brian D.; Rizzolo, Daniel J.; Wright, Kenneth G.; Schmutz, Joel A.
ABSTRACT: A variety of methods such as night-lighting and lift nets have been used to catch divers (Gavidae), although 24-hour daylight in the Arctic summer and the remote nature of field sites can make the use of these traditional methods impossible. Our research required capture of adult divers at remote locations in northern Alaska. Here we describe a suspended dive-net technique that we used to safely capture territorial White-billed Gavia adamsii and Pacific Divers G. pacifica and that is lightweight and easy to set up. We also were able to capture divers with chicks, and failed breeders, and suggest that this method could be used to catch other territorial aquatic diving birds, especially other diver species.